2007
DOI: 10.1148/radiol.2451061590
|View full text |Cite
|
Sign up to set email alerts
|

Recent Myocardial Infarction: Assessment with Unenhanced T1-weighted MR Imaging

Abstract: The purpose of the study was to prospectively evaluate a T1-weighted technique for detection of myocardial edema resulting from recent myocardial infarction (MI) or intervention. This study was HIPAA compliant and institutional review board approved. Fifteen men and one woman (mean age, 57.8 years+/-11.5 [standard deviation]) were examined with T1-weighted magnetic resonance (MR) imaging and inversion-recovery cine pulse sequence in two groups, recent MI and chronic MI, and gave informed consent. T1 relaxation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 35 publications
2
40
0
Order By: Relevance
“…This corresponds with previous studies 31,32 and can be explained by edema in the infarction. Therefore, any small contrast agent-induced reduction in T1 or T2 in the infarct/border zones may have been canceled by these intrinsic relaxation time differences.…”
Section: Contrast Agentsupporting
confidence: 93%
“…This corresponds with previous studies 31,32 and can be explained by edema in the infarction. Therefore, any small contrast agent-induced reduction in T1 or T2 in the infarct/border zones may have been canceled by these intrinsic relaxation time differences.…”
Section: Contrast Agentsupporting
confidence: 93%
“…The T1 mapping identifies a significant variation between normal and abnormal myocardium. It demonstrates the myocardial fibrosis among different myocardial disorders include ischemia [15], acute/chronic infraction [16], amyloidosis [17], diabetic [18], dilated and hypertrophic cardiomyopathy [19], and heart failure [8].…”
Section: T1 Mapping With Modified Look-locker Inversion "Molli" Recoverymentioning
confidence: 99%
“…T1 maps can be generated any time before or after contrast agent (e.g., gadolinium) administration [12]. The MOLLI sequence has been described, optimized, tested, and retested in phantoms and in large cohorts of healthy volunteers [12,14] as well as being applied in cardiomyopathies [8,15,17,19,20]. In addition, the T1 mapping with MOLLI has been validated against histopathology for assessment of myocardial fibrosis.…”
Section: T1 Mapping With Modified Look-locker Inversion "Molli" Recoverymentioning
confidence: 99%
“…30,31) Water has high T1 value and therefore T1 mapping can detect acute MI and assess the extent of myocardial damage with high sensitivity, specificity, and with significantly lower variability of T1 measurements as compared to T2-weighted (T2W) imaging. [32][33][34] It was also superior to T2W imaging in non STsegment elevation MI (NSTEMI). 33) In an animal study, T1 increases were found to be more pronounced in myocardium that was infarcted than in myocardium that was salvaged by reperfusion.…”
Section: Clinical Applications Of Native T1 Mappingmentioning
confidence: 99%